Hormone replacement therapy affects iron status more than endometrial bleeding in older US women: A role for estrogen in iron homeostasis?. (June 2016) - Miller, Elizabeth M.
Highlights: High iron levels in older women are linked to increased risk of chronic disease. Estrogen has been implicated in iron homeostasis, but its involvement has not been confirmed in human models. Hormone replacement therapy is associated with lower ferritin levels in US women. Reproductive hormones may impact iron physiology in older women. Abstract: High iron levels in women of post-reproductive age may be related to their increased risk of chronic disease as they become older, but the causes of this rise in iron in late life is unclear. Recently estrogen has been implicated in non-human models of iron homeostasis. Studying iron in women who take hormone replacement therapy (HRT) may provide insight into the relationship between iron status and hormonal status in older women. This study examines the association between HRT and iron status in women aged 50+ who took part in the 1999–2000 National Health and Nutrition Examination Survey (NHANES). Data were analyzed using multiple imputation, which corrects for missing data, and complex survey regression, which adjusts for NHANES sampling. Current HRT use was associated with lower ferritin (β = −34.13, p = 0.0002), controlling for potential breakthrough bleeding with a hysterectomy variable. HRT was associated with lower iron stores in women of post-reproductive in the absence of uterine blood loss, indicating potential homeostatic hormonal control of iron status. This research demonstrates the utility of studying clinical hormonal therapy to advance new understandings about the basic biology of iron homeostasis in women.